The need for re-organising the UN-system - Volkmar Köhler (Intereconomics, 1976)
The leadership, as well as the organisational structure and the working routine of the UN in as far as they are mainly concerned with development political questions and international economic cooperation are increasingly coming under cross-fire from critics in all parts of the world. A case in point was the recent interpellation by the group of CDU/CSU members in the German Federal Parliament. The subject of this parliamentary inquiry was the re-organisation of the economic and social sectors of the UN. In the following article the member of Parliament, Dr Volkmar Köhler, explains why the interpellation was tabled. His explanation is followed by the publication of item number 10 of the inquiry and the reply by the Minister of State in the Foreign Office, Hans-Jürgen Wischnewski.
Keywords: 330; Germany